Response to Ideology Takes a Day Off: Althusser and Mass Culture - Janet Staiger (Studies in 20th & 21st Century Literature, 1994)
Chip Rhodes defends Althusser's scientific belief that the subject is a bearer of structures and opposes the humanist claim that the subject functions independently of its contexts. However, recent work in cultural studies examines how identity is constructed and allows us to reconcile the scientific and the humanist view. Ideological interpellation may define our subject positions but we are still able to refuse them. For instance, Rhodes' account of "Ferris Bueller's Day Off" assumes that the subject is a fully interpellated, adolescent, Anglo, middle or upper class, heterosexual male. However, the film also offers various oppositional subject positions, including adolescent female or Hispanic, working class youth.
Keywords: Althusser; Marxist philosophy; ideology; science; humanism; cultural studies; identity; construction of identity; mass culture; Ferris Bueller& #x27; s Day Off; Chip Rhodes